The Relationship Between Knowledge And Characteristics Of Adolescents On Attitudes Towards Early Marriage In Smkn 1 Anyar, Serang District - Nurfazriah, Indah (Papua Medicine and Health Science, 2024)
One of the most significant problems affecting adolescent survival is early marriage, which is a reproductive health issue. However, the rate of underage marriage has been increasing every year for the past few years. In rural areas of Banten Province, 19.55% of the married population is under 16 years old, 28.02% is between 17 and 18 years old, and 28.06% is between 19 and 20 years old, according to data from BPS in 2022. To be legally married, a man must be at least 25 years old and a woman must be at least 21 years old. This study used a descriptive correlational design and a cross-sectional method, which shows that this study is not experimental. A total of sixty-four adolescents participated in this study. The questionnaire was the tool used. The chi-square test was used for data analysis. Data analysis showed a statistically significant correlation between adolescents' knowledge and attitudes regarding early marriage (p = 0.022) and its outcomes (p = 0.055)..